2004
DOI: 10.1021/jo0355404
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of DNA with Phenanthridinium as an Artificial DNA Base

Abstract: A phenanthridinium-containing DNA building block was synthesized as an ethidium nucleoside analogue starting from 3,8-diamino-6-phenyl-phenanthridine. Using this building block, oligonucleotides bearing the phenanthridinium moiety as an artificial DNA base were prepared via automated solid-phase phosphoramidite chemistry. The modified phenanthridinium-containing DNA duplexes were characterized by UV/vis absorption spectroscopy (including the melting behavior), CD spectroscopy, and steady-state fluorescence spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 42 publications
0
72
0
2
Order By: Relevance
“…[ [14,17,18] Deswegen kann das PB-Dimer in DNA als hydrophob und diagonal wechselwirkendes Basenpaar angesehen werden, ähnlich denen von Leumann et al [20] und Häner et al [19] Im Unterschied zu diesen publizierten Beispielen weist das PB-Basenpaar ein charakteristisches Absorptionsund Fluoreszenzsignal auf, das die Baseninteraktion anzeigt.…”
Section: Abbildung 1 Temperaturabhängige Fluoreszenzspektren Von Dna1unclassified
See 1 more Smart Citation
“…[ [14,17,18] Deswegen kann das PB-Dimer in DNA als hydrophob und diagonal wechselwirkendes Basenpaar angesehen werden, ähnlich denen von Leumann et al [20] und Häner et al [19] Im Unterschied zu diesen publizierten Beispielen weist das PB-Basenpaar ein charakteristisches Absorptionsund Fluoreszenzsignal auf, das die Baseninteraktion anzeigt.…”
Section: Abbildung 1 Temperaturabhängige Fluoreszenzspektren Von Dna1unclassified
“…[13,14] DNA1 enthält ein Interstrang-PB-Dimer, wohingegen DNA3 je ein PB-Monomer außerhalb des Doppelstrangs an beiden 5'-Enden trägt. Beide Doppelstränge weisen palindromische Sequenzen auf.…”
unclassified
“…[21][22][23][24][25][26][27][28][29][30][31][32][33] Usually, cyanine dyes or other DNA stains [34,35] have been linked to nucleic acids by means of a flexible tether. Previous work by ourselves and others has shown that the tether plays an important role as far as the responsiveness of fluorescence and the stability of probe-target duplexes are concerned.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, organic chromophores like E can be synthetically incorporated as charge donors into oligonucleotides either by covalent attachment to natural DNA bases or by replacing natural bases or even base pairs (24). Recently, we reported the successful synthetic procedure for DNA duplexes bearing the phenanthridinium heterocycle of E as a base pair surrogate (25,26). Then, we applied the emission of the photoexcited E in combination with oxidative hole transfer (HT) to detect single base pair mismatches in duplex DNA (27).…”
mentioning
confidence: 99%